Prenatal exposure to air pollution is associated with structural changes in the neonatal brain. (April 2023) - Bos, Brendan; Barratt, Ben; Batalle, Dafnis; Gale-Grant, Oliver; Hughes, Emer J.; Beevers, Sean; Cordero-Grande, Lucilio; Price, Anthony N.; Hutter, Jana; Hajnal, Joseph V.; Kelly, Frank J.; David Edwards, A.; et al.
Highlights: Examined effects of prenatal exposure to air pollution on neonatal brain structure. Large study in healthy term born neonates. Prenatal air pollution exposure was associated with altered brain morphology. Abstract: Background: Prenatal exposure to air pollution is associated with adverse neurologic consequences in childhood. However, the relationship between in utero exposure to air pollution and neonatal brain development is unclear. Methods: We modelled maternal exposure to nitrogen dioxide (NO2 ) and particulate matter (PM2.5 and PM10 ) at postcode level between date of conception to date of birth and studied the effect of prenatal air pollution exposure on neonatal brain morphology in 469 (207 male) healthy neonates, with gestational age of ≥36 weeks. Infants underwent MR neuroimaging at 3 Tesla at 41.29 (36.71–45.14) weeks post-menstrual age (PMA) as part of the developing human connectome project (dHCP). Single pollutant linear regression and canonical correlation analysis (CCA) were performed to assess the relationship between air pollution and brain morphology, adjusting for confounders and correcting for false discovery rate. Results: Higher exposure to PM10 and lower exposure to NO2 was strongly canonically correlated to a larger relative ventricular volume, and moderately associated with larger relative size of the cerebellum. Modest associations were detected with higher exposure to PM10 and lower exposure to NO2 and smaller relative cortical grey matter and amygdala and hippocampus, and larger relaive brainstem and extracerebral CSF volume. No associations were found with white matter or deep grey nuclei volume. Conclusions: Our findings show that prenatal exposure to air pollution is associated with altered brain morphometry in the neonatal period, albeit with opposing results for NO2 and PM10 . This finding provides further evidence that reducing levels of maternal exposure to particulate matter during pregnancy should be a public health priority and highlights the importance of understanding the impacts of air pollution on this critical development window.